The impact of population aging on income gaps: Can digital finance play a buffering role? - Zhongyuan Sun; Ying Dong; Guangfeng Ning (PLoS ONE, 2026)
Drawing on the panel data of 284 prefecture-level cities in China spanning from 2011 to 2022, this study empirically examines the impact and underlying mechanisms of population aging on urban income disparities through regression analysis. Additionally, it delves into the moderating role of digital finance in this relationship. The main conclusions are as follows: firstly, population aging has asignificant positive impact on both intra-urban income gap and inter-urban income gap. The heterogeneity analysis indicate that the impact of population aging on the inter-urban income gap cities is more significant in the samples of underdeveloped cities and resource-based cities. Secondly, population aging reduces the labor income share and increases social security expenditure, thus expanding the intra-urban income gap. Meanwhile, population aging enlarges the inter-urban income gap by reducing the technological innovation and impeding industrial structure upgrading. Finally, digital finance effectively alleviates the impact of population aging on the intra-urban income gap and inter-urban income gap. Further research reveals that as the quantile of the intra-urban income gap rises, the marginal impact effect of population aging on intra-urban income gap generally demonstrates a trend of first rising and then declining. Meanwhile, as the quantile of the inter-urban income gap increases, the impact coefficient of population aging on the inter-urban gap tends to decline monotonically.